2019
DOI: 10.1130/g45676.1
|View full text |Cite
|
Sign up to set email alerts
|

The rise of oxygen-driven arsenic cycling at ca. 2.48 Ga

Abstract: The Great Oxidation Event (GOE) at 2.45 Ga facilitated the global expansion of oxidized compounds in seawater. Here, we demonstrate that the GOE coincided with a sharp increase in arsenate and arsenic sulfides in marine shales. The dramatic rise of these oxygen-sensitive tracers overlaps with the expansion of key arsenic oxidants, including oxygen, nitrate, and Mn(IV) oxides. The increase in arsenic sulfides by at least an order of magnitude after 2.45 Ga is consistent with the proposed transition to mid-depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 38 publications
3
23
0
Order By: Relevance
“…2). This is consistent with recent analysis on marine shales, suggesting that arsenate began to accumulate in the ocean only after the Archean eon (10), and compatible with the causal role of the GOE in altering the arsenic chemistry on Earth's surface and driving the genetic expansion of arsenic resistance system.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…2). This is consistent with recent analysis on marine shales, suggesting that arsenate began to accumulate in the ocean only after the Archean eon (10), and compatible with the causal role of the GOE in altering the arsenic chemistry on Earth's surface and driving the genetic expansion of arsenic resistance system.…”
Section: Discussionsupporting
confidence: 91%
“…4). Our results are consistent with geochemical models that predict the predominance of reduced arsenic compounds in the anoxic Archean biosphere (2,3,6,10). Formation of traces of arsenate in the Archean, creating a selective pressure before the GOE (6), could have occurred via microbial mediated arsenite oxidation processes such as anoxygenic photosynthesis (5) or nitrate-dependent respiration (23).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Studies of shales show a significant increase in As(V) before the rise of atmospheric oxygen 27 . This accumulation of oxidized arsenic suggests biological activity and more arsenic cycling during the late Archean.…”
mentioning
confidence: 99%
“…Sequence alignment and crystal structure analysis of vanadium haloperoxidases has revealed that amino acids that bind the vanadate cofactor are conserved with a family of acid phosphatases (Hemrika, Renirie, Dekker, Barnett, & Wever, ; Littlechild, Garcia‐Rodriguez, Dalby, & Isupov, ; Wever & Hemrika, ). Recently, it has been shown that an increase in arsenate (AsO43-false]false]>) in marine shales after 2.45 Ga represented the establishment of an oxidative component to the arsenic cycle and the presence of toxic arsenate in seawater (Fru et al, ). A rise in dissolved vanadate after the GOE follows this trend of selective pressures against microbial communities in the form of oxidized elements.…”
Section: Discussionmentioning
confidence: 99%